Core Concepts in Parenchymal Kidney Disease - Fervenza, Fernando C.; Lin, Julie; Sethi, Sanjeev; Singh, Ajay K. (Springer New York : Imprint: Springer, 2014)
Core Concepts in Parenchymal Kidney Disease provides comprehensive and state-of-the-art information on the diagnosis, treatment, classification and pathogenesis of glomerular and tubulointerstitial diseases.  Chapters feature various clinical scenarios and are authored by a team of renowned experts in the field.  Experienced clinicians and trainees alike will find this authoritative reference to be a valuable resource and contribution to the literature.